Structural, electronic, and optical properties of bulk VxMo1−xS2ySe2(1−y) materials: A first-principle calculations - Melak Birara Dagnaw; Abebe Belay Gemta; Kunsa Haho Habura; Fekadu Tolessa Maremi; Dereje Gelanu Dadi; Tesfaye Feyisa Hurisa; Gemechis Mathewos Fite; Manza Zityab Kasiab (AIP Advances)
Using first-principle DFT calculations (Quantum Espresso), we analyze the structural, electronic, and optical properties of hexagonal V0.5Mo0.5S2ySe2(1−y) alloys (y = 0, 0.25, 0.5, and 0.75). Phonon spectra confirm structural stability, with V/S doping reducing bond lengths, angles, and lattice constants vs pure 2H–MoSe2. Vanadium doping induces a semiconductor-to-metal transition, with GGA (GGA+U) bandgaps of 0.976 (1.156) eV for pristine and 0.326 (1.046) eV for V-doped systems. Increasing sulfur content (fixed x = 0.5) further drives this metallic transition. TD-DFPT-calculated optical properties reveal low extinction coefficients/refractive indices and high reflectivity, suggesting anti-reflective/optical coating applications. The loss function shows redshift at y = 0 but blueshifts at y ≥ 0.25. These tunable properties make the alloys promising for nanoelectronics, IR photodetectors, and optoelectronics.